Teaching Aristotelian Ethics at the Racovian Academy: Considerations around Johann Crell’s Ethica Aristotelica. - LASKOWSKA, ANNA MARIA (Renaissance & Reformation / Renaissance et Réforme)
This article focuses on the Socinian ethical treatise Ethica Aristotelica, written by Johann Crell in c. 1622 in Raków, Poland. It is commonly believed that this work, which systematized the theory contained in Aristotle’s Nicomachean Ethics, was a simple compendium intended for exclusive use at the Racovian Academy, an educational institution that welcomed students of diverse religious backgrounds. However, a careful reading of the treatise shows that behind a veil of Aristotelian thought, controversial elements of the Socinian faith were smuggled into the text. These were primarily the idea of Pelagianism and the belief in the human nature of Christ. In the present article, a careful analysis accompanied by several lines of evidence support the idea that Ethica Aristotelica also represents an instrument for promoting the Socinian faith, initially among the students of the Academy, and then, with the print of the first edition in the Netherlands in 1650, among other European confessions.